A novel technique for the synthesis of pure and doped zinc oxide nanostructures using thermal chemical vapor deposition method / Tamil Many K.Thandavan - Tamil Many, K.Thandavan (2016)

(untitled)
A novel technique for the synthesis of ZnO nanostructures utilizing solid brass as the Zn source and alcohol as the oxygen source is described. Zn vapor obtained from solid brass due to the dezincification process aided by a hotwire were carried to the substrates using Ar gas in an evacuated reaction chamber. Also, crucial for the formation of ZnO nanostructures is the presence of alcohol vapor which seemed to provide the oxygen required. Here, the alcohol molecules dissociated on the hotwire surface to produce radical species for the oxidation of Zn produced from the solid brass source. Doping of the ZnO nanostructures with Mn or Al at different concentration was demonstrated by mixing Mn or Al salts in the alcohol to be carried in the reaction chamber by flowing Ar gas. A study on the deposition time on the synthesis of pure ZnO using methanol has yielded ZnO nanostructures of very good crystal structure with changes in morphology from button-liked mushroom to nanorods and to nanoneedles. Using ethanol, ZnO nanorods with larger diameters were produced. Lower values of strain, stress and energy density were observed for samples produced using methanol compared to ethanol which can be related to the formation of low energy sites of ZnO for higher rate of condensation of more energised particle in ZnO using methanol. ZnO nanostructures synthesised using methanol is suitable for field electron emission applications based on their smaller geometrical structures. Photoluminescence spectroscopy results revealed the existence of defects such as zinc interstitials (Zni), oxygen interstitials (Oi), zinc vacancy (Vzn), singly charged zinc vacancy (VZn-), oxygen vacancy (Vo), singly charged oxygen vacancy (Vo+) and oxygen anti-site defects (OZn) in the grown nanostructures. The Raman scattering results also provided evidence of Mn and Al doping due to peak shift from 145 cm-1 in pure ZnO to an anomalous peak at 140 and 138 cm-1 respectively. Field electron emission studies were performed on pure and Mn doped ZnO nanostructures. The best field electron emission properties were obtained with Mn- iv doped ZnO nanostructures with a threshold electric field of 2.06 Vμm-1, and field enhancement factor of 4548. In summary, the pure and doped ZnO nanostructures that have been synthesized using a novel technique utilizing a solid Zn source in thermal CVD system were analyzed. This technique has the potential for simple and economical patterned growth of ZnO nanostructures and films.